2009
DOI: 10.1073/pnas.0900604106
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification of cell cycle-dependent yeast nucleocytoplasmic shuttling proteins by prediction of composite motifs

Abstract: The cell cycle-dependent nucleocytoplasmic transport of proteins is predominantly regulated by CDK kinase activities; however, it is currently difficult to predict the proteins thus regulated, largely because of the low prediction efficiency of the motifs involved. Here, we report the successful prediction of CDK1-regulated nucleocytoplasmic shuttling proteins using a prediction system for nuclear localization signals (NLSs). By systematic amino acid replacement analyses in budding yeast, we created activity-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
1,046
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,112 publications
(1,088 citation statements)
references
References 36 publications
31
1,046
0
11
Order By: Relevance
“…We therefore wanted to exploit our large‐scale data set in this regard. We used cNLS Mapper (Kosugi et al , 2009) to predict potential signals in the cargos selected for validation and detected these in INTS11, EXOSC10, and RPC3 (Table EV6). We also used the DILIMOT algorithm (Neduva et al , 2005) and simple regular expression pattern matching to extract short linear motifs in an unbiased way.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore wanted to exploit our large‐scale data set in this regard. We used cNLS Mapper (Kosugi et al , 2009) to predict potential signals in the cargos selected for validation and detected these in INTS11, EXOSC10, and RPC3 (Table EV6). We also used the DILIMOT algorithm (Neduva et al , 2005) and simple regular expression pattern matching to extract short linear motifs in an unbiased way.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we introduced point mutations into a predicted importin α-dependent nuclear-localization signal (NLS) in murine ULK1 (aa261-289) that was identified using the cNLS Mapper (Supplementary Figure S7a). 40 Individual arginine (R) and lysine (K) residues within the 29-residue NLS were replaced with alanines (A) and the resulting mutants were screened for their ability to disrupt ULK1's nuclear localization. Immunofluorescence microscopy of transiently transfected 293T cells revealed that unlike WT ULK1, the R266A-ULK1 mutant was excluded from the nuclei, even after H 2 O 2 treatment, and did not alter nuclear localization of PARP1-GFP (Figure 6c).…”
Section: ) (D and E)mentioning
confidence: 99%
“…Next, we screened for an NLS in DPP9-l using the cNLS mapper program, which predicts importin α-dependent nuclear localization signals [40]. Using this program we identified a putative classical monopartite NLS: 2-RKVK-KLRL-9 (consensus sequence = K(K/R)X(K/R), which is located in the amino terminal extension of DPP9-l (Fig.…”
Section: Dpp9-l Is An Active Peptidasementioning
confidence: 99%
“…Silencing experiments show that DPP9 and not DPP8 is rate-limiting for the hydrolysis of prolinecontaining peptides in the cytosol suggesting that DPP9 may have a house-keeping role for amino acid homeostasis [28]. the first identified endogenous substrate of DPP9 was the tumor-related epitope RU1 [34][35][36][37][38][39][40][41][42] . Its hydrolysis by DPP9 results in its limited presentation on MhC class I molecules to the immune system linking DPP9 to the MhC class I antigen presentation pathway [28][29][30].…”
Section: Introductionmentioning
confidence: 99%